Tingkat pendapatan dan pola makan berhubungan dengan status gizi balita di Daerah Nelayan Distrik Jayapura Utara Kota Jayapura - Persulessy, Vonny; Mursyid, Abidillah; Wijanarka, Agus (Alma Ata University Press, 2013)
ABSTRACTBackground: Nutrition has an important role in human life cycle. Undernourishment in infants and underfives can cause growth and development disorder. Development of Papua community begins from village empowerment, such as nutrition improvement, health service, and people’s economy. There are544 fisherman families at District of Jayapura Utara. Main stipend of Papua community consists of rice, sago, hipere, taro and banana. Sago is consumed by the majority of people residing at coastal areas. Nutrition Status Monitoring of Jayapura Municipal Health Office in 2008 indicated that 3.4% of underfiveswere malnourished, 17.8% undernourished, 76% well nourished and 2.8% overnourished.Objectives: To identify correlation between level of income and diet pattern with nutritional status of underfive in fi sherman area of Jayapura District Jayapura Municipality.Methods: The study was observational with cross sectional design. The independent variables were level of income and eating pattern; the dependent variable was nutritional status. The study was undertaken in October-December 2010 at District of North Jayapura, Jayapura Municipality involving 162 underfives (of 12-59 moths), and mothers of underfives as respondents. Data were obtained through questionnaire of income, eating pattern using food frequency questionnaire, nutritional status measured from anthropometrybased on weight/age standard of WHO 2005. Data analysis used bivariate with chi square, multivariate with multiple logistic regression.Results: There was signifi cant correlation between income level with nutritional status with (p=0.000) and between diet pattern with nutritional status (p=0.000).Conclusions: Underfives having parents with sufficient income had better nutritional status than those having parent with insufficient income. Underfives with good diet pattern had better nutritional status than those with poor diet pattern.KEYWORDS: income, diet pattern, nutrition status of underfives, fisherman areaABSTRAKLatar belakang: Secara nasional, prevalensi balita gizi buruk dan kurang menurun sebanyak 0,5% menjadi 17,9%. Prevalensi gizi buruk dan kurang Provinsi Papua menurut Riskesdas tahun 2010 sebanyak 16,3%. Data neraca bahan makanan (NBM) Provinsi Papua secara kuantitas menunjukkan rata-rata peningkatan produksi bahan makanan di antaranya beras, jagung, umbi-umbian. Secara kualitas, energi dan protein melebihi angka kecukupan gizi (AKG), tetapi status gizi buruk dan kurang di Kota Jayapura mencapai 21,2% yang dipengaruhi oleh banyak faktor, yaitu tingkat pendapatan, pola makan, pengetahuan ibu, jumlah anggota dalam keluarga.Tujuan: Untuk mengetahui hubungan antara tingkat pendapatan dan pola makan dengan status gizi balita di daerah nelayan Distrik Jayapura Utara, Kota Jayapura.Metode: Penelitian ini merupakan penelitian observasional dengan rancangan cross sectional. Jumlah sampel sebanyak 162 balita (usia 12-59 bulan) dan ibu balita sebagai responden. Pengumpulan data menggunakan kuesioner tingkat pendapatan, pola makan anak dalam keluarga menggunakan food frequency questionnaire (FFQ), status gizi diukur menggunakan antropometri berdasarkan BB/U standar baku WHO 2005. Analisis data bivariat menggunakan chi-square, sedangkan analisis multivariat menggunakan multiple logistic regression.Hasil: Tingkat pendapatan dengan status gizi menunjukkan hubungan yang bermakna dengan nilai (p=0,000). Pola makan dengan status gizi menunjukkan hubungan yang bemakna yaitu (p= 0,010). Variabel luar pengetahuan ibu dengan status gizi, jumlah anggota keluarga dengan status gizi tidak menunjukkan hubungan yang bermakna, yaitu p>0,05.Kesimpulan: Terdapat hubungan yang bermakna antara tingkat pendapatan dengan status gizi, pola makan dengan status gizi.Tetapi tidak ditemukan hubungan yang bermakna antara pengetahuan ibu dengan status gizi, dan jumlah anggota keluarga dengan status gizi.KATA KUNCI: tingkat pendapatan, pola makan, status gizi balita, daerah nelayan